2016
DOI: 10.5021/ad.2016.28.4.417
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Odontogenic Cutaneous Fistulas

Abstract: BackgroundOdontogenic cutaneous fistula appears as dimpling or a nodule with purulent discharge, usually in the chin or jaw. Affected patients usually seek help from dermatologists or surgeons rather than from dentists. However, clinical symptoms of facial skin fistula without dental problems can lead to misdiagnosis.ObjectiveThe purpose of this study was to investigate the clinical characteristics of patients with odontogenic cutaneous fistulas.MethodsThis retrospective observational study was performed at Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 10 publications
(19 reference statements)
1
36
0
2
Order By: Relevance
“…The diagnosis was elusive in the absence of carious teeth and an unremarkable dental history, a clinical phenomenon reported in 50% of patients [ 4 , 8 – 10 ]. The diagnostic conundrum was compounded by the location of the dental infection to the fistulous aperture and its variability [ 1 , 3 , 9 ]. The nonspecific skin manifestation of an odontogenic cutaneous fistula may mimic a number of other disorders previously mentioned, justifying yet another reason why many patients seek care from a multitude of physicians before an accurate diagnosis is achieved [ 1 , 3 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis was elusive in the absence of carious teeth and an unremarkable dental history, a clinical phenomenon reported in 50% of patients [ 4 , 8 – 10 ]. The diagnostic conundrum was compounded by the location of the dental infection to the fistulous aperture and its variability [ 1 , 3 , 9 ]. The nonspecific skin manifestation of an odontogenic cutaneous fistula may mimic a number of other disorders previously mentioned, justifying yet another reason why many patients seek care from a multitude of physicians before an accurate diagnosis is achieved [ 1 , 3 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic conundrum was compounded by the location of the dental infection to the fistulous aperture and its variability [ 1 , 3 , 9 ]. The nonspecific skin manifestation of an odontogenic cutaneous fistula may mimic a number of other disorders previously mentioned, justifying yet another reason why many patients seek care from a multitude of physicians before an accurate diagnosis is achieved [ 1 , 3 , 7 , 11 ]. Our case demonstrates that failure of medical practitioners to effectively communicate and the lack of knowledge of odontogenic cutaneous fistulas lead to diagnostic and therapeutic misadventures as seen in this patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, previous misdiagnosis or inappropriate medical treatment and repeated recurrence have been shown in a retrospective study of Lee et al . [ 19 ] where 27 of 33 patients were transferred from general clinicians and had experience of one or more recurrence. All these authors have reported how important is the interaction between physicians and dentists to avoid submitting patients to multiple biopsies, antibiotic regimens, and unnecessary surgery, before correct diagnosis and endodontic therapy are in course.…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous sinus tracts are a sequel to pathosis, and the clinician should be able to recognize its primary cause. [ 9 18 19 ] They may appear months or even years after the dental pathology and are often not related to it. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%